Pelatihan Bahasa Rusia Untuk Pelaku Pariwisata di Pantai Melasti, Desa Ungasan - Amalia, Layla Fickri; Sanjiwani, I Gusti Agung Mirah; Anggraheni, Raden Roro Rieta; Kanah, Kanah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The purpose of this service activity is to increase the knowledge and skills of tourism actors on Melasti Beach in Ungasan village, especially regarding the lack of knowledge of foreign language tour operators, including Russian. This community service activity provides tourism training in Russian which is carried out with a combination of foreign language training (Russia) and beach cleaning up. The method of implementing service activities in the form of Russian language training is carried out in several stages so that all the material is managed and utilized properly. The purpose of this activity is because many foreign tourists, especially Russians visiting Bali, require foreign language skills from tour operators, especially Russian. In recent years, the number of Russian tourists visiting Bali has increased, Russian tourists often do not understand English, so as a tourism treatment it is necessary to understand and learn Russian. From the results of the community service activities, it can be seen that the skills and mastery of the Russian language by Melasti Beach tour operators is increasing. The quiz results show that the service program meets the needs of partners and also benefits tourism industry players at Melasti Beach in Ungasan Village.